2019
DOI: 10.1158/2159-8290.cd-19-0270
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids from Astrocytes Activate PPARγ Signaling in Cancer Cells to Promote Brain Metastasis

Abstract: Brain metastasis, the most lethal form of melanoma and carcinoma, is the consequence of favorable interactions between the invading cancer cells and the brain cells. Peroxisome proliferator-activated receptor γ (PPARγ) has ambiguous functions in cancer development, and its relevance in advanced brain metastasis remains unclear. Here, we demonstrate that astrocytes, the unique brain glial cells, activate PPARγ in brain metastatic cancer cells. PPARγ activation enhances cell proliferation and metastatic outgrowt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 49 publications
2
99
0
Order By: Relevance
“…Inflammation and oxidative stress are interrelated factors deeply implicated in the pathogenesis of AD, and excessive ROS inevitably lead to lipid damage [13]. Polyunsaturated fatty acids are rich in the brain [14], and they are particularly prone to peroxidization owing to their high reducibility. ROS could degrade polyunsaturated fatty acids into malondialdehyde [15], which causes DNA damage and toxic stress in cells [16].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Inflammation and oxidative stress are interrelated factors deeply implicated in the pathogenesis of AD, and excessive ROS inevitably lead to lipid damage [13]. Polyunsaturated fatty acids are rich in the brain [14], and they are particularly prone to peroxidization owing to their high reducibility. ROS could degrade polyunsaturated fatty acids into malondialdehyde [15], which causes DNA damage and toxic stress in cells [16].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Importantly, the PGC-1a4 variant retains the activation domain common to other PGC-1a transcript isoforms, which mediates binding to nuclear hormone receptor transcription factors such as PPARγ (Li et al, 2008;Martínez-Redondo et al, 2015;Sonoda et al, 2007). Similar to PGC-1a, dichotomous roles for PPARγ have been described with evidence pointing to oncogenic activity in some cancers but tumor suppressor actions in other cancers, and this is supported by data using PPARγ agonists or antagonists, respectively (Goldstein et al, 2017;Kardos et al, 2016;Khandekar et al, 2018;Zou et al, 2019). We demonstrate here that PGC-1a4 upregulates IGF-1 in a PPARγ-dependent manner in CRTC1-MAML2 positive salivary MEC, which sensitizes these tumor cells to treatment with PPARγ inverse agonists.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study by Zou et al showed that astrocytes have a high content of PUFAs (mainly ARA, mead acid, and DHA) that act as “donors” of PPARγ in the invading cancer cells. In addition, the authors directly added AA into the culture medium and promoted the growth of brain metastatic cancer cells through the PPARγ pathway, enhancing cell proliferation and metastatic outgrowth in the brain [ 108 ]. In addition, DHA and EPA decreased the COX-2 mRNA expression and PGE 2 production; it caused a decrease in migration in a matrigel invasion assay in the human melanoma cell line (70W) that metastasizes to the brain in mice.…”
Section: Importance Of Pufas In Brain Functioning and Brain Cancermentioning
confidence: 99%